1974
DOI: 10.1080/00207597408247089
|View full text |Cite
|
Sign up to set email alerts
|

Social Conformity and Psychological Differentiation

Abstract: HollandThis study examined the role of socialization experiences in the development of psychological differentiation. In each of three countries (Holland, Italy, Mexico) two villages were selected as presenting a contrasting picture with regard to degree of emphasis on conformity to family, religious and political authority. It was hypothesized that within the pair of villages in each country children from the village which stressed social conformity would tend to be more field dependent and show other signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
8

Year Published

1975
1975
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 33 publications
(33 reference statements)
1
40
0
8
Order By: Relevance
“…The analyses of covariance using EFT as the dependent variable (table 2), provides strong evidence in support of the claim in much of the literature (Witkin et al 1974;Witkin and Berry 1975;Nedd and Gruenfeld 1976) that social values emphasizing conformity on the one hand, or self-assertion, on the other, are determinants of field-dependent and field-independent cognitive styles, respectively. Finally, the finding that, of the variables investigated, age is the most important determinant of EFT, appears to challenge the claims made by others (Witkinct al.…”
Section: Discussionmentioning
confidence: 62%
“…The analyses of covariance using EFT as the dependent variable (table 2), provides strong evidence in support of the claim in much of the literature (Witkin et al 1974;Witkin and Berry 1975;Nedd and Gruenfeld 1976) that social values emphasizing conformity on the one hand, or self-assertion, on the other, are determinants of field-dependent and field-independent cognitive styles, respectively. Finally, the finding that, of the variables investigated, age is the most important determinant of EFT, appears to challenge the claims made by others (Witkinct al.…”
Section: Discussionmentioning
confidence: 62%
“…If one looks at the most field-independent subjects with USD scores or less than 2 O , it will be seen that none of them had a significant simple frame effect; and among the remainder with greater mean USD scores only 29 per cent had such an effect, findings similar to those * The present sample as a whole was found to be more field-independent than the college sample in Oltman's (15168) original description of the PRFT. However, Oltman's sample was never claimed to be in any sense a normative one, and subsequent studies employing the PRFT (e.g., Witkin et al 1974) have sometimes found wider inter-sample variations in levels of PRFT performance whose causes are not adequately understood. of Nyborg (1977a).…”
Section: Number Of Subjects With Significant Biasmentioning
confidence: 96%
“…A similar distinction has been made by Bakan (1966) who theorized that whereas a sense of self or agency constitutes the "male principle", a sense of selflessness or communion constitutes the "female principle". Parallel male and female principles have been advanced by other theorists, such as field independence vs field dependence (Witkin 1974), allocentric vs autocentric orientation (Gutman 1965) or outer vs inner space (Erikson 1 964). Women's allegedly greater expressiveness, combined with their lesser instrumentality, has also been linked to theories of sex-differences in achievement motivation and achievement behavior (e.g., Hoffman 1977).…”
Section: Theories Of Sex Differences In Temperamentmentioning
confidence: 98%